Cellulose acetate‐based composites with antimicrobial properties from embedded molybdenum trioxide particles. (24th November 2016) - Shafaei, S.; Dörrstein, J.; Guggenbichler, J.P.; Zollfrank, C.
Abstract: The objective of this research was to develop novel cellulose acetate (biopolymer) composite materials with an excellent antimicrobial activity by embedding molybdenum trioxide particles with unique high specific surface area. High surface area molybdenum trioxide particles were prepared from freshly precipitated molybdenum trioxide dihydrate (MoO3 ·2H2 O) and subsequent calcination at 340°C under H2 /N2 gas. Microbiological evaluation against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa were performed applying a roll‐on test and excellent antimicrobial activities were determined for composites with embedded anhydrous molybdenum trioxide with a high specific surface area. Cellulose acetate composites comprising MoO3 particles can eliminate three harmful bacteria as a result of the release of protons from the material and surface enlargement of the molybdenum trioxide particles. The findings support a proposed antimicrobial mechanism based on local acidity increase due to large specific surface areas. Significance and Impact of the Study: In this study, development of a novel thermoplastic bio‐based composite with excellent antimicrobial surface properties is investigated. To the best of our knowledge, this is the first report to evaluate the antimicrobial properties of molybdenum trioxide embedded into a cellulose acetate as biopolymer matrix. The developed composites might step up to innovative applications used in modern medical and public environments. Abstract : Significance and Impact of the Study: In this study, development of a novel thermoplastic bio‐based composite with excellent antimicrobial surface properties is investigated. To the best of our knowledge, this is the first report to evaluate the antimicrobial properties of molybdenum trioxide embedded into a cellulose acetate as biopolymer matrix. The developed composites might step up to innovative applications used in modern medical and public environments.